Tecnologia educativa para aprendizagem da fisiologia da lactação: criação e validação do conteúdo visual - Ribeiro, Polyana de Lima (2019)
Educational technologies are facilitator resources in the learning process. The application of a visual tool favors the comprehension of knowledge, making the user of knowledge participatory in this process by allowing the visualization of the proposed content. Among the issues addressed, the physiology of lactation is highlighted as essential content for clinical practice, since breastfeeding offers numerous benefits to the maternal-infant health. Therefore, the present study has as general objective: To create the visual content of an educational technology for lactation physiology learning and to validate the content with expert judges. Method: Methodological study conducted by the conceptual framework of Knowledge Translation to the action to develop a tool/product of knowledge. The creation took place in the period from March to October 2018 in partnership with the Center for Educational Technology of the Federal University of Santa Maria. The script for the animation was developed from the identification of the imagistic content of the physiology of lactation and from the selection of key-images through a search in textbooks and manuals developed by the Ministry of Health, in the National Digital Library of Brazil, Virtual Health Library and SciELO books. The validation took place from October to November 2018 when were invited around 100 professionals experts in the subjects of breastfeeding or maternal-infant health and with experience in teaching, research or assistance. These professionals were reached through the International Baby Food Action Network, International Board of Lactation Consultant Examiners, International Network for Nursing in Child Health, and Educational Technology Studies Network, and through the “snowball” technique the sample was composed of 27 expert judges that answered a Likert type questionnaire in an online platform. Results: The product was developed from the animation technique to favor the learning from the representation of the organs, hormones and nerve impulses, the main elements of the physiology of lactation attributed to a complex, hard to understand subject. Additionally, the technology articulates a part recorded in video to locate the target of the content to be learned. In the validation, the technology obtained a global Content Validity Index of 0.84. Conclusion: The visual educational technology for promotion of the learning of lactation physiology is validated in content to introduce this subject. This tool of technological support can be inserted as an auxiliary resource to health education actions, and may have positive impact to the practice of breastfeeding.